Recent topics on ethical issues in psychiatry, mental care and welfare - Takahashi, Kiyohisa (Psychiatria et neurologia Japonica, 2002)
This lecture focuses on several ethical issues on psychiatry research and psychiatric practice. The most important issue in ethics is informed consent in both the national guidelines on ethics in genomic study and epidemiological studies determined by the Ministry of Health, Welfare and Labor, Ministry of Education, Culture, Sports, Science and Technology and Ministry of Economy, Trade and Industry. They recommend researchers to obtain consent from subjects making free voluntary decisions after they are fully provided with the necessary information and explanation. The guidelines on ethics in genomic study strongly recommend organizing an ethical committee committed by several extramural members from the fields of law, social or human sciences. On the other hand, the guidelines on ethics in epidemiological study provide how to obtain informed consent in detail according to how projects are carried out. Strict requirements of informed consent tend to inhibit medical research conduct, in particular a research on post-mortem brain, which is one of the important research areas for elucidation of pathogenesis and pathophysiology of mental disorders. Recently a new trend to organize a brain bank by donation of the patient who has given consent before death. This is a proper way to collect post-mortem brain overcoming the ethical problems and it is our hope that this trend will develop in our country. Disclosure of medical records to patients is one of the most recent and debated issues in psychiatric practices. In 1999, the Ministry of Health and Welfare started investigations on whether medical records should be disclosed to patients. The report of the committee strongly recommends accelerating the disclosure of medical records. Responding to this report, several medical organizations issued a guideline. Recently, we carried out a questionnaire survey on the disclosure rate of medical records in the psychiatric departments of both medical school hospitals and national mental hospitals, where special committees have been organized to determine the disclosure of the medical records when a patient demands it officially. Contrary to our expectation the rate of disclosure demands was very low in both medical schools and national mental hospitals. The average number was only less than one case in medical schools, and less than 0.5 cases in national mental hospitals. It was speculated that patient requests demanding the disclosure of the records are mostly managed by the doctor in charge without consulting the special committee. Looking back the process of debate on the disclosure of medical records, several important issues, such as notice of diagnosis, informed consent, management of records, standardization of medical records, financial support to establish management system of medical records and so on, remain to be further examined thoroughly.